Nonlinear Riparian Interactions Drive Changes in Headwater Streamflow - Sarah K. Newcomb; Sarah E. Godsey (Water Resources Research)
Abstract As drought and wildfire frequency increase across the western United States, our ability to predict how water resources will respond to these disturbances depends on our understanding of the feedbacks that maintain watershed function and streamflow. Previous studies of non‐perennial headwater streams have ranked drivers of low‐flow conditions; however, there is a limited understanding of the interactions between these drivers and the processes through which these interactions affect streamflow. Here, we use stream water level, soil moisture, sap flow, and vapor pressure deficit data to investigate ecohydrological interactions along a mountainous headwater stream. Correlation and cross‐correlation analyses of these variables show that ecohydrological interactions are (a) nonlinear and (b) interconnected, suggesting that analyses assuming linearity and independence of each driver are inadequate for quantifying these interactions. To account for these issues and investigate causal linkages, we use convergent cross‐mapping (CCM) to characterize the feedbacks that influence non‐perennial streamflow. CCM is a nonlinear, dynamic method that has only recently been applied to hydrologic systems. CCM results reveal that atmospheric losses associated with local sap flow and vapor pressure deficit are driving changes in soil moisture and streamflow (p < 0.01) and that atmospheric losses influence stream water more directly than shallow soil moisture. These results also demonstrate that riparian processes continue to affect subsurface flows in the channel corridor even after stream drying. This study proposes a nonlinear framework for quantifying the ecohydrologic interactions that may determine how headwater streams respond to disturbance.